CGMP mediates short- and long-term modulation of excitability in a decision-making neuron in Aplysia. (14th September 2018) - Goldner, Amanda; Farruggella, Jesse; Wainwright, Marcy L.; Mozzachiodi, Riccardo
Highlights: We analyzed the modulation of excitability of Aplysia decision-making neuron B51 by cGMP. Another cyclic nucleotide, cAMP, has been previously shown to increase B51 excitability. cGMP injection induced both short-term (45 min) and long-term (24 h) decrease of B51 excitability. Nitric oxide decreased B51 excitability via the activation of the soluble guanylyl cyclase. These findings propose a model of bidirectional modulation of excitability by distinct cyclic nucleotides. Abstract: In elementary neural circuits, changes in excitability can have a strong impact in the expression of a given behavior. One example is provided by B51, a neuron with decision-making properties in the feeding neural circuit of the mollusk Aplysia . The excitability of B51 is bidirectionally modulated by external and internal stimuli in a manner that is consistent with the corresponding induced changes in feeding behavior. For example, in operant reward learning, which up-regulates feeding, B51 excitability is increased via a cAMP-dependent mechanism. Conversely, following training protocols with aversive stimuli, which down-regulate feeding, B51 excitability is decreased. In this study, we tested the hypothesis that B51 decreased excitability may be mediated by another cyclic nucleotide, cGMP. Our results revealed that iontophoretic injection of cGMP was capable of inducing both short-term (45 min) and long-term (24 h) reduction of B51 excitability. We next investigated which biochemical trigger could increase cGMP cytosolic levels. The neurotransmitter nitric oxide was found to decrease B51 excitability through the activation of the soluble guanylyl cyclase. These findings indicate that a cGMP-dependent pathway modulates B51 excitability in a manner opposite of cAMP, indicating that distinct cyclic-nucleotide pathways bidirectionally regulate the excitability of a decision-making neuron.